2022
DOI: 10.1088/0256-307x/39/4/047301
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Electron Gas with High Mobility Forming at BaO/SrTiO3 Interface

Abstract: Two-dimensional electron gas (2DEG) with high electron mobility is highly desired to study the emergent properties and to enhance future device performance. Here we report the formation of 2DEG with high mobility at the interface between rock-salt BaO and perovskite SrTiO3. The interface consists of the ionically compensated BaO1 – δ layer and the electronically compensated TiO2 layer, which is demonstrated as a perfect interface without lattice mismatch. The so-formed interface features met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Such polarisation, for instance in LaAlO 3 /SrTiO 3 , arises due to the charge sequence in LaAlO 3 atomic layers. However, 2DEG can occur even without charged atomic layers thanks to the presence of spontaneous polarisation in ferroelectric thin films [1][2][3][4][5][6]. This means that the electronic properties of the arising state can be tuned by an external field by changing the direction of the ferroelectric dipoles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such polarisation, for instance in LaAlO 3 /SrTiO 3 , arises due to the charge sequence in LaAlO 3 atomic layers. However, 2DEG can occur even without charged atomic layers thanks to the presence of spontaneous polarisation in ferroelectric thin films [1][2][3][4][5][6]. This means that the electronic properties of the arising state can be tuned by an external field by changing the direction of the ferroelectric dipoles.…”
Section: Introductionmentioning
confidence: 99%
“…Even more significant is that changing the polarization direction is able to affect the magnetization inside a ferromagnetic film [8]. The Fe/BaTiO 3 heterostructure has been widely investigated as a simple example of a model system of ferromagnetic/ferroelectric combination [5,8,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the maximum magnetic moment created by an oxygen vacancy located at the LAO/STO interface is 0.2 μ B per Ti atom located in the vicinity of a defect [ 12 ]. Despite the great interest in heterostructures over the past two decades and a substantial amount of research, this area is still fascinating and attracts attention with the discovery of new phenomena [ 13 , 14 , 15 , 16 , 17 ]. To enhance the interfacial magnetism, it is necessary to use magnetic insulators as part of heterostructures to create a spin-polarized 2DEG.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is to have defects in the structure, which is not a complicated task since defects are ubiquitous in most experiments with oxide heterostructures growth. Even more promising is the manipulation of conducting states by an external electric field using ferroelectric materials [ 13 , 14 , 15 , 16 , 17 ], as well as the implementation of the inverse magnetoelectric effect, when the magnetization can be changed by an electric field [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Numerous studies have reported on the 2DEG and its creation or manipulation from a variety of oxide heterojunctions for decades. [5][6][7][8][9][10][11][12][13][14] In general, formation of a 2DEG in complex oxide superlattice requires expensive preparation including the pulsed laser deposition or molecular beam epitaxy. Meanwhile, the single-atomic layer graphene exfoliated from bulk graphite opened up the field of 2D materials.…”
mentioning
confidence: 99%